Inovasi Teknologi Pengolahan Ikan Salai Berbasis Energi Biomassa dengan sistim ruang pembakaran berbentuk parabola Dan Implementasinya pada UKM MINA SALAI KUARAN Di Kelurahan Air Dingin Kecamatan Bukit Raya Kota Pekanbaru - Muhammad, Juandi; Gimin, Gimin; Hasibuan, Saberina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Biomass energy, which comes from plants, is used as a heating source in fish processing. This community service activity is focused on the smoked fish processing industry in Air Dingin Village, Bukit Raya District, Pekanbaru, with the aim of analyzing the optimal use of biomass energy. The main source of energy is the rambutan tree trunk, which gives a distinctive aroma to smoked fish. The method used is direct training to apply new techniques in this industry, with raw materials of patin fish (30 kg) and catfish (40 kg). The smoking process takes 24 hours, producing efficient and high-quality smoked fish, seen from its bright color and fragrant aroma. This Community Partnership Program (PKM) aims to improve the quality and quantity of production of the UKM MINA SALAI KUARAN business group. It is hoped that the quantity of production will increase by 50%, while the social aspects of the community are strengthened through online marketing using social media such as Twitter and Facebook. Thus, this business has the potential to become more independent and improve the welfare of the local community.